The problems of music teaching in Croatia in profesional journals of the second half of the 19th century - Košta, Tomislav, profesor crkvene glazbe (Array, 2019)
After the civil revolution of 1848 and the awakening of national consciousness, in the midst of the struggle of small nations for independence as well as for the official use of the national language, music was introduced into schools as an obligatory subject called Singing. During that period, the first songbooks, textbooks and manuals in Croatian language were created. The period was the one of institutional reform of education evidenced in the adoption of important school laws that set the foundation for the development of national education. The First School Law of 1874 and the Second School Law of 1888 particularly influenced the teaching of music in Croatia. In this context, we analyze the publications in the professional journals of the time relating to the problems of music education in elementary school. The pivotal journal of pedagogy, where we note the largest number of professional publications at the time in Croatia, was called Napredak. There were other journals as well, such as Prosvjeta, Smilje, Školski prijatelj and Hrvatski učitelj, but hardly any articles on music teaching can be found in them. We also mention the annual Izvješća Kraljevske preparandije u Zagrebu, where Vjenceslav Novak, the most prominent music pedagogue of the second half of the 19th century used to write. The professional publications that we analyze provide important information on the beginnings of the development of contemporary music teaching in Croatian schools and on the problems encountered by music pedagogues and practitioners of that time.